Ritual, Rejuvenation Practices, and the Experience of Aging in Early Chinese Religion. (7th July 2017) - Tavor, Ori
Abstract : Scientific advances in the field of biomedicine have fundamentally changed the ways in which we think about our bodies. Disease, aging, and even death, are no longer seen as inevitable realities but as obstacles that can be controlled, and in some cases even reversed, by technological means. The current discourse, however, can be enriched by an investigation of the various ways in which the aging process was perceived and explained throughout human history. In this article, I argue that in early China, the experience of aging and the challenges and anxieties it produced played a constitutive role in the shaping of religious culture. Drawing on a variety of medical, philosophical, and liturgical sources, I outline two models of aging: one that presented aging, and especially the loss of virility, as an undesirable but solvable condition that can be reversed with the aid of various rejuvenation techniques, and a more socially conscious model that depicted aging as a process of gradual social ascension, a natural but fundamentally unalterable condition that should be accepted, marked, and even celebrated through ritual. I conclude by demonstrating the legacy and lasting influence of these models on two of the most fundamental tenets of Chinese religion: the pursuit of longevity and the ideal of filial piety.